Durability Prediction of Lightweight Concrete Structure Considering Pre-Compressive Stress Based on Probabilistic Theory - The Truyen Tran; Thu Minh Tran; Xuan Tung Nguyen; Ba Thanh Vu; Quang Vu Le (Journal of Applied Science and Engineering)
This study aims to present the results of anticipation of lightweight concrete durability when exposed to a chloride environment under pre-compressive load. The research employs Keramzit aggregate as the coarse aggregate for lightweight concrete. Following a 28-day curing period in water, the concrete specimens undergo varying levels of pre-compressive stress. Rapid Chloride Permeability Testing is then conducted to ascertain the chloride diffusion coefficient. The study posits a correlation between the chloride diffusion coefficient and precompressive stress levels, drawing from the experimental findings. Furthermore, Monte-Carlo simulation is employed to assess the influence of stochastic variables on the corrosion likelihood of concrete structures using lightweight aggregates. These stochastic variables encompass the chloride diffusion coefficient, surface chloride concentration, critical chloride concentration, concrete protection layer thickness, and a coefficient contingent on environmental conditions, to appraise the operational lifespan of lightweight concrete structures.